Simulação computacional do colapso em edifícios de aço com múltiplos andares devido à ação do incêndio - Baroni, Ariadne (2017)
This work presents a structural analysis, made through a numerical model conceived in SAP2000, which objective is to study the behavior of a steel structure of multiple floors subject to localized fire action. This paper presents the evaluation of three different compartments under high temperatures in order to verify overall displacements and the redistribution of efforts in the structure due to fire action. Thereby, it was possible to predict in the structure where the local action of compartmentalized fire is more severe. With the increase in the use of steel buildings, the present study may present significant contributions for the prediction of local collapse in structures. From the results obtained, it was possible to assess, in a simplified way, how the thermal action resulting from fire influences the overall behavior of the structure.